Combined TOPEX/Poseidon TEC and ionosonde observations of negative low-latitude ionospheric storms - K. J. W. Lynn; M. Sjarifudin; T. J. Harris; M. Le Huy (Annales Geophysicae, 2004)
Ionospheric storms showing a strong depression in daytime foF2 values were sought which penetrated to low-latitudes, as identified by vertical ionosondes operating at Darwin and Townsville over the period 1992-1998. The 32 storms thus identified showed a seasonal occurrence peaking near the equinoxes with a bias to the summer side. Of these storms, three (27 March 1995, 25 October 1997, 8 November 1997) combined Australian and South East Asian ionosonde observations with local afternoon TOPEX/Poseidon measurements of TEC. The equatorial anomaly is usually well developed at this time of day and consequently these storms were chosen for detailed study. The TOPEX/Poseidon satellite provided vertical profiles of the ionosphere across both hemispheres, thus allowing the totality of storm behaviour to be observed for the first time at low-latitudes and related directly to the ionosonde observations. The three storms were remarkably consistent in their behaviour, the negative ionospheric storm day followed some 24-36h after the beginning of a magnetic storm and the development of the equatorial anomaly was suppressed. However, the suppression of the equatorial anomaly was not the main cause of the strong depression in foF2 observed by the Southern Hemisphere ionosondes. The latter was associated with an additional bite-out in both TEC and foF2 that occurred on the southern side of the magnetic equator. None of the three storms produced any major negative disturbance outside the range of normal variability of TEC and foF2 at the northern latitude sites for which data was available, despite the absence of the anomaly. The satellite measurements show the strength of the anomaly to be highly variable from day-to-day and anomaly peaks are frequently not present even on magnetically quiet days. Thus, an absence of anomaly peaks is contained within the normal variability of non-storm days. The north-south asymmetry and seasonal occurrence are consistent with an enhancement of the normal summer-to-winter system carrying compositional changes induced by energy inputs at auroral latitudes to equatorial latitudes not usually reached. The ability of associated atmospheric and/or electric field changes to coincidentally switch off the equatorial E region electrojet remains to be explained, as indeed does the large range of variability in equatorial anomaly development from day-to-day evident in the TEC measurements outside periods of geomagnetic disturbance. Some possible positive storm effects occurring on the day preceding the negative storm phase are also noted.